Influence of TIG welding processing parameters on mechanical properties of austenitic stainless steel using Taguchi analysis. (2023) - Rajaravi, C.; Ganesh, B.; Lakshmanan, S.; Gobalakrishnan, B.
Abstract: Austenitic stainless steel 316 is used in a variety of applications. Due to the lack of post-hardening operations such as strong intergranular corrosion resistance, annealing, and increased toughness, ASS 316 are chosen in the construction of thermal power plants, pressure vessels, and vehicle components. The effects of process parameters such as current and travel speed, as well as weld filler rod diameter, are explored in this paper. The Taguchi approach was used to optimize the output parameters in this paper. Weld speed and input power are the process parameters studied during TIG welding. The experimental results indicated that flux welding might increase the weld depth/width ratio and reduce the HAZ range, leading in less angular distortion in the weld men. The Taguchi approach was employed in this work to optimize the output parameters.a result of which the weld men have reduced angular distortion.